THE EFFECT OF DIGITAL PAYMENT SYSTEMS ON CONSUMER SPENDING BEHAVIOR AND FINANCIAL STABILITY - Rosid, Abdul (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The growth of digital payment systems has changed consumption behavior and financial stability across various demographic groups. This research aims to explore how digital payment systems influence shopping behavior among different age groups, income levels and education levels. Using a Systematic Literature Review (SLR) approach, this research analyzed 43 relevant articles from various academic databases. Findings show that younger generations, especially Millennials and Gen Z, tend to spend more due to the ease of digital transactions, while older generations are more skeptical about adopting this technology. In addition, income and financial literacy factors play an important role in determining an individual's response to digital payment systems. This research provides insights for stakeholders, including regulators and the fintech industry, to design more inclusive and effective strategies for managing the impact of digital payment systems.